Metformin: update on mechanisms of action on liver diseases - Ruan, Gaoyi; Wu, Fangquan; Shi, Dibang; Sun, Hongxia; Wang, Fangyan; Xu, Changlong (Frontiers in Nutrition, 2023)
Substantial attention has been paid to the various effects of metformin on liver diseases; the liver is the targeted organ where metformin exerts its antihyperglycemic properties. In non-alcoholic fatty liver disease (NAFLD), studies have shown that metformin affects the ATP/AMP ratio to activate AMPK, subsequently governing lipid metabolism. The latest research showed that low-dose metformin targets the lysosomal AMPK pathway to decrease hepatic triglyceride levels through the PEN2-ATP6AP1 axis in an AMP-independent manner. Metformin regulates caspase-3, eukaryotic initiation factor-2a (eIF2a), and insulin receptor substrate-1 (IRS-1) in palmitate-exposed HepG2 cells, alleviating endoplasmic reticulum (ER) stress. Recent observations highlighted the critical association with intestinal flora, as confirmed by the finding that metformin decreased the relative abundance of Bacteroides fragilis while increasing Akkermansia muciniphila and Bifidobacterium bifidum. The suppression of intestinal farnesoid X receptor (FXR) and the elevation of short-chain fatty acids resulted in the upregulation of tight junction protein and the alleviation of hepatic inflammation induced by lipopolysaccharide (LPS). Additionally, metformin delayed the progression of cirrhosis by regulating the activation and proliferation of hepatic stellate cells (HSCs) via the TGF-β1/Smad3 and succinate-GPR91 pathways. In hepatocellular carcinoma (HCC), metformin impeded the cell cycle and enhanced the curative effect of antitumor medications. Moreover, metformin protects against chemical-induced and drug-induced liver injury (DILI) against hepatotoxic drugs. These findings suggest that metformin may have pharmacological efficacy against liver diseases.